How long can you run at critical power intensity? An analysis of the time to exhaustion in trained athletes - Cuartero, J. O.; Ruiz-Alias, S. A.; Ñancupil Andrade, A. A.; Carrillo, D. J.; García Pinillos, F. (European Journal of Human Movement, 2026)
To date, speed has been the main external load variable in running, ignoring variables that can now be controlled by power. This means that concepts widely studied in cycling, such as critical power (CP), must now be deeply analyzed in running, considering the specificity of the discipline and the differences between both sexes. Thus, the aim of the study was twofold, i) to determine the individual time to exhaustion (TTE) at CP intensity in a group of highly trained athletes under field conditions and ii) to analyze the influence of sex in the TTE at CP. A local group of 37 highly trained athletes, 18 males and 19 females performed a CP test and a TTE test at CP intensity in two different field test sessions. Small ES but no significant differences (p = 0.163; ES: 0.45) between males (22.5 [6.9] minutes) and females (19.1 [7.8] minutes) were observed in the TTE test at CP. A high individual variability was observed, ranging the TTE from 9.2 to 32.5 minutes in males, and 9.3 to 36.1 minutes in females. This variability may be due to the standard error of the estimate.